Effect of two-level decompressive procedures on the biomechanics of the lumbo-sacral spine: an ex vivo study - Montanari, Sara; Serchi, Elena; Conti, Alfredo; Barbanti Bròdano, Giovanni; Stagni, Rita; Cristofolini, Luca (Frontiers in Bioengineering and Biotechnology, 2024)
Hemilaminectomy and laminectomy are decompressive procedures commonly used in case of lumbar spinal stenosis, which involve the removal of the posterior elements of the spine. These procedures may compromise the stability of the spine segment and create critical strains in the intervertebral discs.Thus, this study aimed to investigate if decompressive procedures could alter the biomechanics of the lumbar spine. The focus was on the changes in the range of motion and strain distribution of the discs after two-level hemilaminectomy and laminectomy.Twelve L2-S1 cadaver specimens were prepared and mechanically tested in flexion, extension and both left and right lateral bending, in the intact condition, after a two-level hemilaminectomy on L4 and L5 vertebrae, and a full laminectomy. The range of motion (ROM) of the entire segment was assessed in all the conditions and loading configurations. In addition, Digital Image Correlation was used to measure the strain distribution on the surface of each specimen during the mechanical tests, focusing on the disc between the two decompressed vertebrae and in the two adjacent discs.Hemilaminectomy did not significantly affect the ROM, nor the strain on the discs. Laminectomy significantly increased the ROM in flexion, compared to the intact state. Laminectomy significantly increased the tensile strains on both L3-L4 and L4-L5 disc (p=0.028 and p=0.014) in ipsilateral bending, and the compressive strains on L4-L5 intervertebral disc, in both ipsilateral and contralateral bending (p=0.014 and p=0.0066), with respect to the intact condition.In conclusion, this study found out that hemilaminectomy did not significantly impact the biomechanics of the lumbar spine. Conversely, after the full laminectomy, flexion significantly increased the range of motion and lateral bending was the most critical configuration for largest principal strain.